Commentary on ‘Honorary authorship epidemic in scholarly publications? How the current use of citation-based evaluative metrics make (pseudo)honorary authors from honest contributors of every multiauthor article.’ - Anderson, S. (Journal of medical ethics, 2013)
Kovacs calls for collaborating teams to indicate the proportional credit that each author of a multi-authored paper deserves.1 This approach addresses the problem of giving each of the co-authors full (and therefore inflated) credit for the article when their publication records are assessed. This problem is, however, a weakness in the evaluation system, not in the publication system, and it will not be solved by the proposed strategy.As the author notes, publication records are critical to decisions on hiring, promotion, tenure, salaries and allocation of research resources. At each of these points, what matters most is the quality of the candidate's work, which cannot be adequately assessed by quick counts of articles, even when the counts are weighted by numbers of citations or impact factors. Some institutions and departments perform careful reviews; others …